Peran Guru dalam Meningkatkan Keaktifan dan Pemahaman Siswa Melalui Active Learning pada Mata Pelajaran PAI - Reva Fadilla; Sariva Aulia Rabani; Gusmaneli Gusmaneli (Educational Journal, 2026)
This study aims to describe the role of teachers in enhancing student engagement and understanding in Islamic Religious Education (IRE) through the application of the Active Learning model. The main issue addressed is the dominance of conventional teaching methods, which leads to low student participation and contextual understanding of religious material. Using a descriptive qualitative method, this study examines how teachers shift their roles from mere information providers to facilitators and motivators. The results indicate that the implementation of various active learning strategies fosters dynamic two-way interaction, making students more enthusiastic and enabling them to internalize PAI values deeply rather than merely memorizing them. In conclusion, teachers’ creativity in applying active learning is highly effective in transforming the classroom atmosphere into a more inclusive environment and significantly improving the quality of student learning outcomes